Capillary electrophoresis of peptides - Kasicka, V (Electrophoresis, 1999)
This article gives a review of the recent developments in capillary electrophoresis (CE) of peptides. New approaches to the theoretical description of electromigration behavior of peptides are described, and methodological aspects of CE separations of peptides such as selection of separation conditions, sample treatment, suppression of peptide adsorption to the capillary wall and specificities of CE separation modes are discussed. Progress in application of high performance detection schemes, namely laser-induced fluorescence and mass spectrometry, in peptide separations by CE is presented. Applications of different CE techniques, zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography and electrochromatography to peptide analysis, preparation and physicochemical characterization are demonstrated.
Keywords: chemické modely; Models, Chemical; peptidy; Electrophoresis, Capillary; Peptides; Stereoisomerism; stereoizomerie; elektroforéza kapilární